2016
DOI: 10.1016/s2095-3119(16)61419-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis, single nucleotide polymorphisms within SIRT4 and SIRT7 genes and their association with body size and meat quality traits in Qinchuan cattle

Abstract: Silent information regulator 2 (Sir2) proteins, or sirtuins, are nicotine adenine dinucleotide (NAD)-dependent deacetylases that connect metabolism with longevity in lower organisms. In mammals, there are seven Sir2 homologs, namely, silent information regulators (SIRT1-7). SIRT4 and SIRT7 genes play a crucial role in regulating lipid metabolism, cellular growth and metabolism. This suggests that they are potential candidate genes for affecting body size and meat quality traits in animals. Hence, this study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…In mammals, polymorphisms of the SIRT7 gene are involved in human longevity (Donlon et al, 2018), highaltitude adaptation (Y. , and Parkinson's disease (Jesús et al, 2013). Because of the key role of SIRT7 in regulating lipid metabolism (Yoshizawa et al, 2014;Tang et al, 2015), glucose metabolism (Jiang et al, 2017;Ye et al, 2017), and cell growth or differentiation, the relationship between the polymorphisms tested and sheep growth traits were also analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, polymorphisms of the SIRT7 gene are involved in human longevity (Donlon et al, 2018), highaltitude adaptation (Y. , and Parkinson's disease (Jesús et al, 2013). Because of the key role of SIRT7 in regulating lipid metabolism (Yoshizawa et al, 2014;Tang et al, 2015), glucose metabolism (Jiang et al, 2017;Ye et al, 2017), and cell growth or differentiation, the relationship between the polymorphisms tested and sheep growth traits were also analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…That showed that the SIRT7 gene behaved as a key enzyme for lipid metabolism, which could be related to deposition of lipids in mammals. Previously, in Qinchuan cattle, two SNPs were identified in the SIRT7 gene (exon 6 and exon 7): SNP2 (g.3587C > T) and SNP3 (g.3793T > C), which are linked with body traits and meat quality [15]. Furthermore, SNP2 (g.3587C > T) was determined in the SIRT7 gene, and it was concluded that it can be linked with body size traits including a higher hip width and greater ultrasound loin muscle area in Qinchuan cattle [11,15].…”
Section: Gene Polymorphism Vs Slaughter Value and Beef Qualitymentioning
confidence: 99%
“…Previously, in Qinchuan cattle, two SNPs were identified in the SIRT7 gene (exon 6 and exon 7): SNP2 (g.3587C > T) and SNP3 (g.3793T > C), which are linked with body traits and meat quality [15]. Furthermore, SNP2 (g.3587C > T) was determined in the SIRT7 gene, and it was concluded that it can be linked with body size traits including a higher hip width and greater ultrasound loin muscle area in Qinchuan cattle [11,15]. Additionally, the same Chinese researchers found that the local cattle with an SNP3-C 3C3 genotype (g.3793T > C) had a significantly higher hip width, body length, ultrasound loin muscle area, chest circumference, and back fat thickness compared with those with the SNP3-T 3T3 genotype ( p < 0.05).…”
Section: Gene Polymorphism Vs Slaughter Value and Beef Qualitymentioning
confidence: 99%
See 1 more Smart Citation